Genera key to Trichoptera (Insecta) larvae from Western slope of the Andes, Lima, Peru - Huamantinco, Ana A. (2010)
A key for identification of Trichoptera larvae of the last development instar is proposed. The biological material was collected in streams located in the middle and high river basins of Lima, Western Slope of the Andes. A synopsis for genera and species for Peru is presented for each family found in this study.